Adulto femenino de 58 años con hipertensión arterial estadio II - De la Rosa Mayorga, Lisbeth del Carmen (2019)
Hypertension is considered a recognized health problem because it is caused by an increase in the force of pressure made by the heart on the arteries, triggering complications. This case study is about a 58-year-old female patient diagnosed with arterial hypertension about 6 years ago who goes to the hospital because of: tachycardia, headache, chest pain, drowsiness, fatigue, dizziness and blurred vision. The biochemical tests reveal the following values: cholesterol (240mg / dl) triglycerides (211mg / dl) the doctor diagnoses arterial hypertension in stage 2. Patient receives medical prescription (losartan 50mg), the same that must be fulfilled with an adequate nutritional treatment that will help to reduce pressure levels. A nutritional intervention was applied based on a comprehensive diagnosis which consists in developing a nutritional assessment since the patient presents grade I obesity with android body composition, moderate cardiovascular risk, related to genetic factors evidenced by altered levels of alternate pressure and hyperlipidemia. A dietary plan is prescribed: Low sodium diet of 1605 kcal / day low in saturated fats, high in potassium with 25 gr of fiber / day, divided into 5 times of food / day with which it was possible to decrease the weight of the patient and the levels of blood pressure, taking a weekly control within a period of 9 months according to their daily requirements, in addition to achieving new dietary habits and an adequate lifestyle in the patient.